Collapse of a Crawling Peg Regime in the Presence of a Government Budget Constraint - Savastano, Miguel (IMF Working Papers; Working Paper ;, 1991)
This study extends the research on balance-of-payments crises by investigating the dynamics of the collapse of a crawling exchange rate in the presence of an explicit link between the fiscal deficit and domestic credit. It shows that such an exchange rate regime is characterized by two potential steady-state equilibria. This introduces an ex-ante indeterminacy regarding the timing and magnitude of the speculative attack on international reserves in the event of a sustained inconsistency between the country's fiscal and exchange rate policies. The paper discusses the conditions that would define the actual timing of the regime's breakdown.